PENGARUH PENGALAMAN KERJA DAN KEPATUHAN TERHADAP KODE ETIK PADA KUALITAS AUDIT MELALUI SKEPTISISME PROFESIONAL AUDITOR - Oktarini, Komang; Ramantha, I Wayan (E-Jurnal Akuntansi; Vol 15 No 1 (2016), 2016)
The purpose of this study is to determine the effect of work experience and adherence to a code of conduct on the quality of the audit by the auditor's professional skepticism. This research was conducted on the entire public accounting firm located in the province of Bali. Samples are taken as many as 81 people auditors, with nonprobability methods of sampling and purposive sampling technique. Data collected through questionnaires. The analysis technique used is Partial Least Square (PLS). Based on the analysis found that the work experience and adherence to a code of ethics positive effect on the audit quality through an auditor's professional skepticism.
Keywords: Audit Quality, Work Experience, Compliance with the Code of Ethics, Professional Skepticism